Effects of irradiation processing of specialty protein products on nursery pig performance - J C Woodworth; M J Webster; B W James; D E Real; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
Three hundred weanling pigs (initially 13.4 lb and 20 ± 2 d of age) were used in a 14-d growth assay to determine the effects of irradiation processing of specialty protein products on nursery pig performance. Overall, irradiated of AP 920 and Peptide-Plusâ„¢ resulted in increased ADG compared to nonirradiated products. Irradiation of Peptide-PlusÂ® improved feed efficiency compared to its nonirradiated form. Also, ADG was greater for pigs fed diets containing ProtiOneâ„¢ and DPS 30 and tended to increase with AP 920 compared to those fed the control diet. In addition, feed efficiency was improved for pigs fed diets containing ProtiOneâ„¢, DPS 30, Peptide-Plusâ„¢, and spray-dried egg compared to those fed the control diet. Therefore, adding specialty protein products to diets in most cases improved growth performance, and irradiation processing improved growth performance with certain specialty protein products.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Nursery pigs; Irradiation; Speciality protein